Indigenous Early Career Researchers in Australian Universities Our Stories - Trudgett, Michelle; Page, Susan; Povey, Rhonda; Locke, Michelle; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This open access book explores the key barriers and facilitators to advancing meaningful and fulfilling academic careers in the higher education sector for Australian Indigenous doctoral graduates. It focuses on the career trajectories of Indigenous early career researchers who have participated in the Developing Indigenous Australian Early Career Researchers study, funded by the Australian Research Council (ARC). It delves into a deeper understanding of the professional development requirements of Indigenous Early Career Research academics and presents a new set of knowledge which incorporates Indigenous standpoints, thus creating new avenues for Indigenous early career researchers to articulate their living experiences and perspectives for the benefit of their colleagues, in the present and the future. This book also provides a model of best practice collaborative approach through its methodology, method, and structural design. The various chapters present first-hand experience with an Indigenist methodological approach, including access to respectful use of culturally appropriate terminology, modelled by the authors and carefully footnoted with explanatory notes. Its writing is also guided by ethical principles concerning Indigenous Intellectual Property Rights. This book serves as a compendium of critique for current and future Indigenous early career researchers, as well as an encouragement for mentors and advocates for equity and parity for Indigenous academics in higher education. Through the voices of Indigenous early career researchers, this book positions universities well to facilitate improved Indigenous outcomes and to continue to pursue educational equity within the higher education sector. .
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Education, Higher; Inclusive education; Education and state; Higher Education; Inclusive Education; Educational Policy and Politics